HACCP NELLA PRODUZIONE PRIMARIA: CONSIDERAZIONI TECNICHE E LEGISLATIVE IN APICOLTURA E NELLA PRODUZIONE DI MIELE CONFEZIONATO (Rassegna di Diritto, Legislazione e Medicina Legale Veterinaria, 2017)
The HACCP method developed by NACMCF and spread by the Codex Alimentarius Guidelines was developed and planned to be usefully implemented in all the food chain production steps starting right from the primary production. The Reg (EC) 852/2004 does not require the application of the HACCP method according to Codex Alimentarius in the primary production, nevertheless it requires however the FBO (Food Business Operator) to implement general requirements on hygiene for primary production and associated operations. The aims of this study are: A) Performing a critical analysis of some legislative elements about the "primary production" and "self-control" in the beekeeping and honey production field, with particular reference to Lombardia Region regulation aspects. B) To prove the possibility to develop a simple, effective self-control plan complies with the requirements of Reg (EC) 852/2004 Art.5 and easy to apply in a small, hobby classified beekeeping situated in a Lombardia Region hilly area.